2019
DOI: 10.1029/2018wr023415
|View full text |Cite
|
Sign up to set email alerts
|

Tracking CO2 Plumes in Clay‐Rich Rock by Distributed Fiber Optic Strain Sensing (DFOSS): A Laboratory Demonstration

Abstract: Monitoring the migration of pore pressure, deformation, and saturation plumes with effective tools is important for the storage and utilization of fluids in underground reservoirs, such as geological stores of carbon dioxide (CO2) and natural gas. Such tools would also verify the security of the fluid contained reservoir‐caprock system. Utilizing the swelling strain attributed to pressure buildup and the adsorption of supercritical CO2 on clay minerals, we tracked the fluid plume in a natural clay‐rich Tako sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 60 publications
5
38
0
Order By: Relevance
“…Once the rock is saturated, any further changes in strain are nearly fully controlled by the pore pressure (poroelastic deformation), as is clear in Figure 8b. By incorporating Langmuir adsorption, Zhang et al (2019) developed a two-phase fluid flow and poromechanical coupled model to simulate flow and deformation.…”
Section: Discussion: Possible Role Of Clay Swelling In Rock Deformationmentioning
confidence: 99%
See 4 more Smart Citations
“…Once the rock is saturated, any further changes in strain are nearly fully controlled by the pore pressure (poroelastic deformation), as is clear in Figure 8b. By incorporating Langmuir adsorption, Zhang et al (2019) developed a two-phase fluid flow and poromechanical coupled model to simulate flow and deformation.…”
Section: Discussion: Possible Role Of Clay Swelling In Rock Deformationmentioning
confidence: 99%
“…The strain was amplified relative to natural rock in the subsurface, which is often initially hydrated. However, for a two-phase fluid flow regime (supercritical CO 2 and brine) in which the rock sample was initially saturated with brine, Zhang et al (2019) showed in an experimental study that the adsorption-induced strain change can be remarkably sensitive to the fluid migration front. The induced swelling may be an indicator for the migration of the fluid plume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations